Transcreation and the challenges of the translation industry - Jaworski, Marcin (Creativity in Business Practice. Part 2, 2019)
Nowadays, customer satisfaction and their personalized expectations are by far the biggest challenge for today's service companies, including the translation industry. This chapter discusses the basic role of transcreation and its place among the services provided by international translation agencies. Orientation for continuous development, striving to gain a competitive advantage in the dynamically changing environment of the organization. The chapter aims to present the possibility of using transcreation and its place in the current market situation in the translation industry and to show its practical application.